2023
DOI: 10.5114/hivar.2023.131466
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with progression from HIV to death in patients receiving antiretroviral therapy in Southern Iran: a 21-year survival analysis and follow-up study

Sima Afrashteh,
Mohammad Fararouei,
Haleh Ghaem
et al.

Abstract: Introduction:The expansion of human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) epidemic has been considered a serious issue globally, and the disease is currently a major contributing factor to morbidity and mortality rates in many developing countries. This study aimed to investigate survival rate of HIV-positive patients, and its' contributing factors among individuals receiving antiretroviral therapy in Southern Iran. Material and methods:A prospective cohort study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Moreover, the possible role of unemployment in treatment failure was found among our patients, which showed that unemployment may reduce treatment adherence. A job is a valid characteristic of an individual’s socioeconomic status in society; therefore, unemployment is a risk factor for the incidence of treatment failure [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the possible role of unemployment in treatment failure was found among our patients, which showed that unemployment may reduce treatment adherence. A job is a valid characteristic of an individual’s socioeconomic status in society; therefore, unemployment is a risk factor for the incidence of treatment failure [ 61 ].…”
Section: Discussionmentioning
confidence: 99%